Family Support, Entrepreneurial Experience, and Risk-Taking Propensity as Predictors of Entrepreneurial Success: The Mediating Role of Motivation - Adri, Jamal; Harubali, Harubali (Universitas Negeri Makassar, 2025)
Entrepreneurship has become an important pathway for addressing graduate unemployment while fostering innovation, job creation, and economic resilience. This study examines the direct and indirect effects of family support, entrepreneurial experience, and risk-taking propensity on entrepreneurial success, with motivation serving as a mediating variable. A quantitative explanatory approach was employed using survey data collected from 97 respondents selected through proportional random sampling. The analysis focuses on understanding how personal, experiential, and social factors contribute to entrepreneurial success both directly and through motivational mechanisms. The findings indicate that family support, entrepreneurial experience, and risk-taking propensity have significant positive effects on entrepreneurial success, both independently and indirectly through motivation. The results further suggest that motivation functions as an important psychological driver that strengthens the contribution of family encouragement, prior entrepreneurial exposure, and willingness to take risks to business success. These findings imply that entrepreneurial success is not shaped solely by technical capability or prior experience, but also by the presence of supportive social environments and strong internal motivation. This study highlights the importance of integrating entrepreneurial development programs with efforts to strengthen motivation, practical experience, and supportive ecosystems. The findings provide practical implications for higher education institutions and entrepreneurship development programs in designing interventions that better prepare emerging entrepreneurs for sustainable business achievement.